Reliability assessment on ultimate and serviceability limit states and determination of critical factor of safety for underground rock caverns - Zhang, Wengang (2012)
The observational design method which uses extensometers to measure the displacements during cavern construction and then adopt these data for back analysis does not always guarantee satisfactory performance because the displacements provide little information about the strength to stress ratio that ultimately determines the stability of the rock caverns. In this study, both the ultimate and serviceability limit states are investigated by means of the Finite Difference program FLAC3D. The global factor of safety obtained using the shear strength reduction technique is used as the criterion for the ultimate limit state and the calculated percent strain around the opening is adopted as the serviceability limit state criterion. High deformability, low shear strength and the high in situ stress state are the major factors that govern the underground rock cavern stability and serviceability. Through the identification of the key influencing parameters for calculating the factor of safety and the percent strain, numerical experimentations are performed in accordance with the methodology of 2k factorial design, from which polynomial regression models are developed for each rock mass condition. The First-Order Reliability Method (FORM) was used to determine the probability of failure for the limit states. Through the use of the automated spreadsheet search algorithm to determine the design point, to meet the different target performance levels, the required minimum FS is obtained and termed as the critical value. This proposed approach enables a cost-effective analysis to be conducted for a rational design of underground rock caverns.